2016
DOI: 10.1039/c6ra05561c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic NiO nanoparticles confined within open ends MWCNTs: a novel and highly active catalyst for hydrogenation and synthesis of imines

Abstract: A new nanocatalyst has been synthesized by confining magnetic nickel nanoparticles within carbon nanotubes (CNTs) and characterized by XRD, TEM, Raman and VSM. The character of the nanocatalyst passivated with a gas mixture was that it can be stored safely in air below 150 C and needs no activation prior to use. In the catalytic test, a nickel oxide nanocatalyst confined inside the Multi-walled carbon nanotubes nanochannels (NiO/MWCNTs-in) was found to be a highly efficient and reusable catalyst for the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…N-Phenyl-1-(4(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl) [21] ; 72% yield. N-(4-fluorophenyl) [24] ; 99% yield. [27] ; 99% yield.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…N-Phenyl-1-(4(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl) [21] ; 72% yield. N-(4-fluorophenyl) [24] ; 99% yield. [27] ; 99% yield.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The performance of the unsupported Ni‐acac catalyst was compared with previously reported Ni‐based supported catalysts and Raney‐Ni (Table S1). We found that our system shows better results when comparing the reaction conditions, yield and selectivity [17,18,44,22,37–43] . Moreover, the stability of the Ni‐acac catalyst is superior to those Ni‐based systems since it maintained great yield and selectivity even using it up to the fifth cycle.…”
Section: Resultsmentioning
confidence: 83%
“…We found that our system shows better results when comparing the reaction conditions, yield and selectivity. [17,18,44,22,[37][38][39][40][41][42][43] Moreover, the stability of the Ni-acac catalyst is superior to those Ni-based systems since it maintained great yield and selectivity even using it up to the fifth cycle. Most of the other supported catalysts showed good performance just for one catalytic run.…”
Section: Chemistryselectmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Furthermore, increasing restrictions imposed by governments and the United Nations protocols with the aim of eliminating toxic chemical processes require adopting safer procedures. In this context, researchers have studied systems with metals, such as Mn, [30] Ni, [31][32][33] Ru, [34,35] Co, [36][37][38] Rh, [39][40][41] Ir, [42][43][44][45] Pd, [46,47] and Pt [48] immobilized on zeolite, [49,50] silica, [50,51] polymers, [52][53][54] alumina, [55] magnetite, [39,[56][57][58][59] and carbon. [60] These systems exhibit moderate to excellent conversion and selectivity, especially in the hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%